2012
DOI: 10.5194/we-12-49-2012
|View full text |Cite
|
Sign up to set email alerts
|

Biomass explains the intensity of facilitative – not competitive – interactions: three intraspecific tests with annuals

Abstract: Abstract. Despite efforts to discern the role of plant size in resource competition, the circumstances under which size-dependent plant-plant interactions occur are still unclear. The traditional assumption is that competition intensifies with increasing neighbour size. However, recent studies suggest that the size (biomass) dependence of competitive interactions is strongest at very low biomass levels and becomes negligible after a certain threshold neighbour biomass has been reached. We searched for the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The formation of these patterns has been thought to result from self-organization processes between plants [Lefever and Lejeune, 1997;Lejeune et al, 1999;HilleRisLambers et al, 2001;von Hardenberg et al, 2001;Rietkerk et al, 2002Rietkerk et al, , 2004D'Odorico et al, 2007;Gilad et al, 2007;Getzin et al, 2014]. Self-organization arises in vegetated contexts mainly due to competitive and/or facilitative effects of individual plants on their neighbors, often in tandem and at differing ranges [Lefever and Lejeune, 1997;Kéfi et al, 2007;Barbier et al, 2006Barbier et al, , 2008Brooker et al, 2008;Bailey, 2011;Ariza and Tielbörger, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of these patterns has been thought to result from self-organization processes between plants [Lefever and Lejeune, 1997;Lejeune et al, 1999;HilleRisLambers et al, 2001;von Hardenberg et al, 2001;Rietkerk et al, 2002Rietkerk et al, , 2004D'Odorico et al, 2007;Gilad et al, 2007;Getzin et al, 2014]. Self-organization arises in vegetated contexts mainly due to competitive and/or facilitative effects of individual plants on their neighbors, often in tandem and at differing ranges [Lefever and Lejeune, 1997;Kéfi et al, 2007;Barbier et al, 2006Barbier et al, , 2008Brooker et al, 2008;Bailey, 2011;Ariza and Tielbörger, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Some facilitation studies made important contributions to the management and conservation of a single keystone species. Arrieta and Suárez (2001) reported the facilitative effect of nurse Ilex aquifolium (holly) shrubs and successfully related the observed spatial pattern to differences in light, dispersal, and disturbance, with important implications for holly conservation in southern Europe. Other studies had a large-scale vision and embraced the study of plant-plant interactions at landscape levels, even comparing similar habitats across continents.…”
mentioning
confidence: 86%
“…Reid et al (2010) performed a systematic review of the ecological literature on cushion plants, which were found to be real champions of facilitation due to the microclimatic conditions found within their compact and prostrate canopies and the particular importance of those more favorable conditions on the highly stressful environments that they inhabit, making them keystone species in the ecosystems they inhabit. Ariza and Tielbörger (2012) found that biomass explained the intensity of facilitative interactions but not of competitive ones. The assumption that increased biomass results in increased competition was challenged by intra-specific tests with three different annual herbs, for which a consistent pattern of size-dependent facilitation interactions was observed across life stages, explained as predominantly aboveground facilitation via water stress alleviation and predominant below-ground competition for water.…”
mentioning
confidence: 96%
“…This is characterized by the positive effect in which at least one of the local species benefits from interactions. A direct implication of this result is that plants with higher biomass may not prevail in the long term [13,14].…”
Section: Introductionmentioning
confidence: 94%